Impact of environmental factors on the emergence, transmission and distribution of Toxoplasma gondii. Issue 1 (December 2016) - Yan, Chao; Liang, Li-Jun; Zheng, Kui-Yang; Zhu, Xing-Quan
Abstract Toxoplasma gondii is an obligate intracellular protozoan that poses a great threat to human health and economic well-being worldwide. The effects of environmental factors such as changing climate and human activities on the ecology of this protozoan are being discovered. Accumulated evidence shows that changes of these environmental factors can exert influence on the occurrence, transmission and distribution ofT. gondii. This article reviews studies from different geographical regions with varying climates, social cultures and animal welfare standards. It aims to illustrate how these environmental factors work, highlighting their importance in influencing the ecology ofT. gondii, as well as providing clues which may contribute to preventing transmission of this important zoonotic pathogen.